Poetry Analysis of Osundare s Random Blues: Using Speech Act Theory - Rutmintauli Simanjuntak; Purnama Rika Perdana; Muhammad Ilham Ali (English Education Postgraduate Program, Universitas Negeri Manado, 2023)
Osundare s involvement in performative poetry is an attempt to fulfill her social responsibilities and connect with her community as her collective poetry is expressed through performance The rhetoric of his poems and the structure of their presentation explains why he uses the techniques and resources of the African oral tradition in many of his poems The purpose of this study is to explore the intertextual relationship between the second generation of Nigerian artists and the new Nigerian artists in terms of colonial influences and relationships This study shows that poet Niyi Osundare is a second generation iconoclast through which he influenced the poetic landscape of contemporary Nigeria This study shows that contemporary poets are not significant and methodologically influential to other secular poetic texts so the aesthetic principle of poetry is emphasized when the dialogue between texts is seen in the form of Osundare poetry Osundare tells about the paradigm shift of intertextual relations from a vertical point of view and the artistic practices preserved from the colonial period are the vertical practices of the postcolonial space The research is qualitative in nature and primarily analyzed primary and secondary data from the literature original research and literature review This study also uses poststructuralist intertextuality as a theoretical framework to explore the extent of intertextual relationships This study suggests that in order to understand recent Nigerian poetry in English there is an urgent need to explore the history of their intertextuality Beyond the intertextual dimension this study demonstrates that the symbiotic relationship between power and traditional formation provides an ontological framework for examining the aesthetic experience of recent English poetry in Nigeria < em>< p> < p>